Islamization and Arabization of Berber tribes in Northern Africa - Stewart, Jeremy; Doležal, Tomáš; Müller, Karel B., 1972-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2018)
Introduction: Analysis of the current and past situation regarding Berber tribes, Islam, and Arabization. Analysis of government sanctioned programs both precolonial and postcolonial. Chapter 1: Differences between Berbers, Arabs, and practitioners of IslamChapter 2: MoroccoChapter 3: LibyaChapter 4: TunisiaChapter 5: AlgeriaConclusion: AlRumi, Aisha. Libyan Berbers Struggle to Assert Their Identity Online. Arab Media & Society (2009): n. pag. Web. 22 Oct. 2016. <http://beta.arabmediasociety.com.preview.sqgd.net/articles/downloads/20090506151750_AMS8_Aisha_al-Rumi.pdf>.Kostiner, Joseph, Harvard University, Massachusetts Institute of Technology. Tribes and State Formation in the Middle East. N.p.: U of California, 1990. Print.MaddyWeitzman, Bruce. Contested Identities: Berbers, Berberism and the State in North Africa. The Journal of North African Studies, 29 Mar. 2007. Web. 22 Oct. 2016. <https://www.researchgate.net/publication/261679115_Contested_Identities_Berbers_%27Berberism%27_and_the_State_in_North_Africa>.MaddyWeitzman, Bruce. The Berber Identity Movement and the Challenge to North African States. Austin: U of Texas, 2011. Print.Willis, Michael J. Politics and Power in the Maghreb: Algeria, Tunisia and Morocco from Independence to the Arab Spring. New York: Columbia UP, 2012. Print.
Vedoucí práce: Tomáš Doležal
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses